Code Switching Used by English Lecturers During Teaching as Found in Padang State University - Widya Fhitri (JURNAL ARBITRER, 2017)
This research focuses on the study of the types of code switching and the reasons for lecturers to use the code switching that is based on Wardaugh's theory and supported by Gumperz. The data was collected by using field method, with several steps, namely: following the lecturer, recording techniques, field recording, and interviews. From several data were examined, it was found three types of code switching. Conversations type is a type of code switching that often appear, followed by the type of situational and metaphorical. In addition, it was found seven reasons for the use of code switching in teaching and learning, namely the influence of students who first use the Indonesian language, ignorance of the students to the lecturers' explanation , the emphasis on the previous statement, search the attention of the students because they make noise in the classroom, liquefaction the tense atmosphere with a little joke, forgetfulness some of the terms in English, and no equivalent word in English when giving an example of a lesson.